Dual-comb-based asynchronous pump-probe measurement with an ultrawide temporal dynamic range for characterization of photo-excited InAs quantum dots. (4th May 2020) - Asahara, Akifumi; Arai, Yuto; Saito, Tomohiro; Ishi-Hayase, Junko; Akahane, Kouichi; Minoshima, Kaoru
Abstract: A dual-comb-based asynchronous optical sampling (ASOPS) pump-probe measurement system is demonstrated for characterizing the relaxation dynamics in a photo-excited self-assembled InAs quantum dot (QD) semiconductor. Although the photo-excited QD material has multiple complex relaxation processes, the transient transmittance responses (from femtoseconds to nanoseconds) are successfully obtained within a sub-second short acquisition time by using the ASOPS system. This is achieved with high stability and an extremely wide temporal dynamic range of approximately 10 5 . The utility of the developed system is demonstrated as a powerful and easy-to-use measurement tool for studying the complex photo-excited dynamics of QD materials.